PENINGKATAN KUALITAS LAYANAN JASA KULINER BAGI PEREMPUAN DI DESA WISATA BEJIHARJO, KARANGMOJO, GUNUNG KIDUL - Sujarwo, -; Widyaningsih, -; Tohani, Entoh (INOTEKS: Jurnal Inovasi Ilmu Pengetahuan,Teknologi, dan Seni, 2015)
Quality improvement activities culinary services for women in tourismis one to build awareness of culinary services in tourism and hygienic quality;and provide knowledge and skills in the provision of services and the hygienicquality culinary supporting the community in Bejiharjo. This is due to the lack ofcompetence of the provision of services to satisfy customers' culinary tourismand the presence of the economic potential that has not been widely used. Thetraining activities carried out by the adult learning approach to the 25 women inHamlet Karangmojo, Bejiharjo, Karangmojo, Gunung Kidul. Learning is donein four stages which include: awareness of the group, identifying the needs oflearning, vocational learning and culinary services, and a reflection of the implementation of activities. The results showed that the activity enhancement activities capable of providing meaningful learning experiences in which therehas been a change in the behavior of the target group. The target group can understand the importance of services and the optimal culinary master productive skills in the culinary field. Therefore, the development of the target group needs to be more continuous and involves all parties involved